2015
DOI: 10.4046/trd.2015.78.4.436
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ectopic Adrenocorticotropic Hormone Syndrome in Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC), which originated from neuroendocrine tissue, can develop into paraneoplastic endocrine syndromes, such as Cushing syndrome, because of an inappropriate secretion of ectopic adrenocorticotropic hormone (ACTH). This paraneoplastic syndrome is known to be a poor prognostic factor in SCLC. The reason for poor survival may be because of a higher risk of infection associated with hypercortisolemia. Therefore, early detection and appropriate treatment for this syndrome is necessary. But… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Ectopic Cushing syndrome (ECS) is defined by the production of ACTH by a tumor originating outside the pituitary glands. This entity was first described in 1965 and it accounts for 5%-10% of cases of spontaneous Cushing's syndrome [5]. Most of these tumors have been small-cell tumors of the lung or carcinoid tumors, and less frequently, neoplasms emerging from the embryonic structures and tissues with endocrine function, including pheochromocytoma, thymic tumors, pancreatic carcinoma, and anaplastic thyroid carcinoma [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic Cushing syndrome (ECS) is defined by the production of ACTH by a tumor originating outside the pituitary glands. This entity was first described in 1965 and it accounts for 5%-10% of cases of spontaneous Cushing's syndrome [5]. Most of these tumors have been small-cell tumors of the lung or carcinoid tumors, and less frequently, neoplasms emerging from the embryonic structures and tissues with endocrine function, including pheochromocytoma, thymic tumors, pancreatic carcinoma, and anaplastic thyroid carcinoma [6].…”
Section: Discussionmentioning
confidence: 99%
“…As our patient presented, hypokalemia and metabolic alkalosis are the usual findings that suggest the presence of increased ACTH production and lead to subsequent confirmation testing. [5] Patients suffering from ectopic adrenocorticotropic hormone production have high ACTH levels (>20 ng/L), high cortisol levels that are not suppressed by high dexamethasone dosages (8 mg per day), and they have negative response of the pituitary gland to the corticotrophin-releasing hormone. In a few examples, patients having excess ACTH production can be appropriately suppressed by high-dose dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al suggested that controlling the high cortisol level and then administering systemic chemotherapy may achieve longer survival 12. With the exception of systemic chemotherapy, ketoconazole, metyrapone, etomidate, mitotane, and mifepristone can be used to reduce circulating glucocorticoids 5.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of ECS consists of complete imaging evaluation with contrast-enhanced CT scan of the chest, abdomen, and pelvis, plasma adrenocorticotropic hormone (ACTH) concentration greater than 15 pg/ mL, non-suppressed morning cortisol level after highdose dexamethasone suppression test, elevated 24-hour urine-free cortisol level, and sampling of tissue, if found on CT scan. Several studies have suggested that systemic chemotherapy achieves more prolonged survival (30)(31)(32)(33). Other medications, including etomidate, mitotane, ketoconazole, metyrapone, and mifepristone are used to reduce circulating glucocorticoids (34).…”
Section: Ectopic Cushing's Syndrome (Ecs)mentioning
confidence: 99%